2015
DOI: 10.3168/jds.2014-8348
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Use of a portable, automated, open-circuit gas quantification system and the sulfur hexafluoride tracer technique for measuring enteric methane emissions in Holstein cows fed ad libitum or restricted

Abstract: The objective of this study was to measure enteric CH4 emissions using a new portable automated open-circuit gas quantification system (GQS) and the sulfur hexafluoride tracer technique (SF6) in midlactation Holstein cows housed in a tiestall barn. Sixteen cows averaging 176 ± 34 d in milk, 40.7 ± 6.1 kg of milk yield, and 685 ± 49 kg of body weight were randomly assigned to 1 out of 2 treatments according to a crossover design. Treatments were (1) ad libitum (adjusted daily to yield 10% orts) and (2) restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Dorich et al (2015) found average CH 4 emission from lactating dairy cows (n =16) measured using the GreenFeed and SF 6 technique were similar, but the SF 6 technique showed higher variability in the relationship between CH 4 (g/d) and DMI (r 2 = 0.17, P < 0.02), compared with GreenFeed (r 2 = 0.42, P < 0.01). The authors attributed this higher variability for SF 6 measurements to the high concentration of background gases combined with poor barn ventilation.…”
Section: Short-term Measurements Using Automated Head Chambers (Greenmentioning
confidence: 89%
See 2 more Smart Citations
“…Dorich et al (2015) found average CH 4 emission from lactating dairy cows (n =16) measured using the GreenFeed and SF 6 technique were similar, but the SF 6 technique showed higher variability in the relationship between CH 4 (g/d) and DMI (r 2 = 0.17, P < 0.02), compared with GreenFeed (r 2 = 0.42, P < 0.01). The authors attributed this higher variability for SF 6 measurements to the high concentration of background gases combined with poor barn ventilation.…”
Section: Short-term Measurements Using Automated Head Chambers (Greenmentioning
confidence: 89%
“…The authors concluded that the visit hours had a significant effect on estimated CH 4 emission, particularly for animals whose number of visits were low and irregular during the day. Methane emission may be biased by sampling times; generally being highest after feeding and during rumination bouts (Storm et al, 2012;Hegarty, 2013;Dorich et al, 2015;Hristov et al, 2015b). As explained in Branco et al (2015) and Hristov et al (2015a, b), best results with GreenFeed are obtained when the number and timing of animal visits are controlled by the investigator, which is easily achievable in a tie-stall barn situation.…”
Section: Short-term Measurements Using Automated Head Chambers (Greenmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with lactating dairy cows, it was concluded that CH 4 emissions measured by the AHCS were similar to literature values derived from respiration chambers and between animal variability (CV of 11 to 12%; repeatability of 0.64 to 0.81) was also within the range reported for respiration chambers 10 . In a recently-published study with lactating cows, AHCS produced a smaller CV than the SF 6 method (14.1 to 22.4% vs. 16.0 to 111% for SF 6 ) 13 . In a 12-week experiment conducted at the Pennsylvania State University with 48 lactating dairy cows, in which rumen CH 4 production was inhibited by 30% (P < 0.001), we concluded that AHCS and the SF 6 method produced similar CH 4 emission results: 319 to 481 g/cow per day (mean = 374 g/d; SEM = 15.9; CV = 13%) and 345 to 485 g/cow per day (mean = 396 g/d; SEM = 29.8; CV = 23%) for AHCS and SF 6 , respectively 14 .…”
Section: Discussionmentioning
confidence: 86%
“…In the cow selection phase of the study, a group of 24 multiparous Holstein dairy cows housed in tiestalls were adapted to the GreenFeed unit (C-Lock Inc., Rapid City, SD) that quantifies CH 4 production with minimal disturbance (Dorich et al, 2015). Adaptation was measured once daily for 7 d with a score (on a scale of 1 to 5) reflecting a cow's willingness to move her head forward and keep it in the hooded trough area of the GreenFeed unit when enticed with small amounts of concentrates offered over a 5-min period.…”
Section: Cows Experimental Design and Dietary Treatmentsmentioning
confidence: 99%